If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(x+12)=59
We move all terms to the left:
(x+12)-(59)=0
We get rid of parentheses
x+12-59=0
We add all the numbers together, and all the variables
x-47=0
We move all terms containing x to the left, all other terms to the right
x=47
| x²+5x+32=0 | | 10z+7=77 | | (3h-1=17) | | )3h-1=17) | | 7y+5=-37 | | K=n2+9n+1 | | 37+54+x=180 | | 8x-11x=-27 | | 43+22+x=180 | | M+6=6m | | 3x-6-10x+5+6x+8+10=-x | | -7x+18=60 | | -34=3(x-5)+2 | | 4·(x+3)=7x+3x= | | 9b-18=9 | | 3-(2-x)=2x+4 | | x/5=15x | | -19+2x=-7 | | 7x-12=37x | | 3·(2x-4)=10x+4 | | 3(5x-2)=25.5 | | 27-x=11+5x | | r+4=3r | | -8d+11+6d=19 | | 14w-14=14 | | 3·y=96 | | 13w-14=-w+14 | | 10-2s=5-8 | | y=1E+07+4 | | t^2+2t+5=0 | | 2(x-3)(x-5)=0 | | 4a+3+6=32 |